Solid polymer electrolyte with high ionic conductivity via layer-by-layer deposition - Cui, Mengqi (2020)
A novel multilayer system via layer-by-layer (LbL) self-assembly by alternatively packing polyethylene glycol (PEG)-α-cyclodextrin (αCD) complex and poly(acrylic acid) (PAA) via hydrogen-bonding is designed and investigated in this work. The PEG-αCD inclusion complex is obtained by supramolecular interaction. Multilayer films with different ratios of αCD are fabricated, and the growth behavior, morphology, thermal properties and electrical properties of the resultant LbL films are systematically characterized. The films with PEG-αCD complex and PAA as building blocks show high ionic conductivity reaching up to 2.5×10-5 S cm-1 under room temperature (52%RH), which is almost two orders magnitude higher than the PEG/PAA films under the same conditions. The PEG-αCD15/PAA films also possess high water retention due to the large amount of hydroxyl groups carried by αCD, which enables the films, after exposed to a high humidity environment, to maintain a high ionic conductivity under low humidity environment. This PEG-αCD/PAA LbL system provides an insight for designing polymer based solid state electrolyte and its application towards electrochemical devices.